Use of expected-value parameters for estimating length-weight relationship in fishes - ., Prajneshu; Ravichandran, S (Indian Journal of Fisheries, 2011)
Nonlinear estimation procedures are generally employed for determining the length-weight relationship in fishes. As no attention is paid to reparameterization of the parameters, the model-data set combination sometimes exhibits an extremely high nonlinear behaviour, i.e. the parameter-effects measure of curvature is very large. The purpose of the present paper is to make use of’expected-value’ parameters which depict close-to-linear behaviour. The methodology is illustrated with the help of data taken from fisheries literature.